Review of the Fundamental Measurement Modalities in Photoacoustic Mechanical Imaging - Xiaohan Shi; Jianqin Sun; Hua Yuan; Liming Li; Haiyang Zhang; Yue Zhao (Photonics)
Photoacoustic (PA) imaging is a non-invasive imaging technique with high optical resolution and acoustic penetration depth, which has been widely used in medical and clinical researches. As an important part in functional PA imaging, photoacoustic mechanical imaging (PAMI) has great potential in visualizing and understanding the local development of pathological process. This review provides lots of PA breakthroughs which have been made in elasticity detection, viscosity detection, and viscoelasticity detection through PAMI techniques. The current research problems, challenges and future development directions were discussed.